Teaching Writing Narrative Text by Using Story Pyramid Strategy for Senior High School Students - Shintya Ferina Putri; Fitrawati Fitrawati (Journal of English Language Teaching, 2020)
Writing is an important skill that is needed in order to share  and convey ideas into written form. As a writer, the students should be able to give their thoughts through writing. However, many students have difficulties in writing the text and they do not know how to generate adn develope their ideas. It is because they are confused to develope their ideas into a paragraph. That is why this paper is conducted on order to explain how to use Story Pyramid Strategy in teaching writing narrative to senior high schools students. Story pyramid is pre-writing activity that is done before writing. It is an outline that contains some instructions to describe the important information from a story such as the main character, the setting and the major events in the plot. It means that this strategy assists students to produce and arrange the ideas clearly before they start writing. it believed that this strategy can help many students in improving their writing ability.